Aquatic Iguana: A Floating Waste Collecting Robot with IoT Based Water Monitoring System - Mirza Turesinin; Abdullah Md Humayun Kabir; Tanzina Mollah; Sadvan Sarwar; Shazzad Hosain (Proceeding of the Electrical Engineering Computer Science and Informatics, 2020)
Water pollution is a major problem worldwide. In order to tackle the pollution and keeping the water resources clean, this paper presents an affordable and advanced floating garbage removing robot called "Aquatic Iguana". The robot moves around the surface of the water and collects floating waste material such as plastic, packets, leaves, etc. Along with the waste-collecting system, the robot also includes water monitoring with pH, turbidity, temperature sensors, and a live streaming feature, increasing the capacity to a greater extent. We have developed this robot to ensure the cleaning of water resources and to create a strong data set of water quality for future predictions. The use of this technology will ensure the safety of all aquatic animals and plants.